Pengalaman Pasien HIV/Aids dalam Menjalani Pengobatan ARV di RSUD Nabire: Literature Review - Allolinggi, Meryana Ambun; Astrid, Maria (LPPM Institut Pendidikan Nusantara Global, 2025)
Antiretroviral (ARV) therapy plays a crucial role in the management of HIV/AIDS, particularly in Regional General Hospitals (RSUD). This article, based on a literature review, explores patients’ experiences while undergoing ARV treatment and the diverse challenges that accompany it. The decision-making process at the beginning of therapy often becomes a difficult stage, as patients face doubts, fears, and social pressures. Nevertheless, adherence to ARV therapy has been proven to bring significant benefits, especially in improving patients’ quality of life and extending life expectancy. On the other hand, social stigma remains a major barrier, both from the surrounding community and within the patients themselves. This stigma affects treatment adherence and patients’ mental well-being. The discussion highlights ethical considerations, clinical effectiveness, and the importance of a holistic approach that integrates physical, psychological, and social aspects of care. Findings emphasize that the success of HIV/AIDS management in RSUD relies not only on the availability of medication but also on comprehensive support systems. Therefore, this article recommends strengthening community education programs, providing psychosocial support services, and equipping healthcare workers with training to become more responsive to patient needs.